Strain Engineering in Highly Mismatched SiGe/Si Heterostructures. (1st November 2017) - Isa, Fabio; Jung, Arik; Salvalaglio, Marco; Dasilva, Yadira Arroyo Rojas; Marozau, Ivan; Meduňa, Mojmír; Barget, Michael; Marzegalli, Anna; Isella, Giovanni; Erni, Rolf; Pezzoli, Fabio; Bonera, Emiliano; et al.
Abstract: In this work we present an innovative approach to realise coherent, highly-mismatched 3-dimensional heterostructures on substrates patterned at the micrometre-scale. The approach is based on the out-of-equilibrium deposition of SiGe alloys graded at an exceptionally shallow grading rate (GR) of 1.5% µm −1 by low energy plasma enhanced chemical vapour deposition (LEPECVD). Fully coherent SiGe/Si crystals up to 6 µm in width were achieved as confirmed by defect etching and transmission electron microscopy (TEM) analyses. The experimental results are supported by calculations of the energy for dislocation formation which indicate that elastic relaxation is energetically favoured over plastic relaxation in the narrower heterostructures. X-ray diffraction measurements show that the SiGe crystals are strain-free irrespective of the stress relieving mechanism which changes from elastic to plastic by increasing their width. The impact of dislocations on the SiGe crystal quality is analysed by comparing the width of X-ray diffraction peaks as a function of the heterostructure size.